Self-assembled silver nanoparticle-DNA on a dielectrode microdevice for determination of gynecologic tumors - Li, Z. (Springer, 2020)
Nanoscale materials have been employed in the past 2 decades in applications such as biosensing, therapeutics and medical diagnostics due to their beneficial optoelectronic properties. In recent years, silver nanoparticles (AgNPs) have gained attention due to their higher plasmon excitation efficiency than gold nanoparticles, as proved by sharper and stronger plasmon resonance peaks. The current work is focused on utilizing self-assembled DNA-AgNPs on microdevices for the detection of gynecological cancers. Human papilloma virus (HPV) mostly spreads through sexual transmittance and can cause various gynecological cancers, including cervical, ovarian and endometrial cancers. In particular, oncogene E7 from the HPV strain 16 (HPV-16 E7) is responsible for causing these cancers. In this research, the target sequence of HPV-16 E7 was detected by an AgNP-conjugated capture probe on a dielectrode sensor. The detection limit was in the range between 10 and 100 aM (by 3Ï estimation). The sensitivity of the AgNP-conjugated probe was 10 aM and similar to the sensitivity of gold nanoparticle conjugation sensors, and the mismatched control DNA failed to detect the target, proving selective HPV detection. Morphological assessments on the AgNPs and the sensing surfaces by high-resolution microscopy revealed the surface arrangement. This sensing platform can be expanded to develop sensors for the detection various clinically relevant targets. Â© 2020, Springer Science+Business Media, LLC, part of Springer Nature.